Netrin-1/DCC Signaling Differentially Regulates the Migration of Pax7, Nkx6.1, Irx2, Otp, and Otx2 Cell Populations in the Developing Interpeduncular Nucleus - García-Guillén, Isabel M.; Alonso, Antonia; Morales-Delgado, Nicanor; Andrés, Belén; Puelles, Luis; López-Bendito, Guillermina; Marín, Faustino; Aroca, Pilar (Frontiers in Cell and Developmental Biology, 2020)
The interpeduncular nucleus (IPN) is a hindbrain structure formed by three main subdivisions, the prodromal (Pro) domain located at the isthmus (Ist), and the rostral and caudal interpeduncular domains (IPR, IPC) within rhombomere 1 (r1). Various cell populations can be detected in the IPN through the expression of the Nkx6.1, Otp, Otx2, Pax7, and/or Irx2 transcription factors. These cell populations follow independent dorsoventral tangential and radial migratory routes targeting the ventral paramedian region of Ist and r1. Here we set out to examine the influence of the Netrin-1/DCC pathway on these migrations, since it is known to regulate other processes of neuronal migration in the brain. To this end, we analyzed IPN development in late gestational wild-type and DCC–/– mice, using mainly in situ hybridization (ISH) to identify the cells expressing each of the aforementioned genes. We found that the migration of Nkx6.1+ and Irx2+ cells into the Pro domain was strongly disrupted by the loss of DCC, as occurred with the migration of Pax7+, Irx2+, and Otp+ cells that would normally form the IPR. In addition, there was mild impairment of the migration of the Pax7+ and Otx2+ cells that form the IPC. These results demonstrate that the Netrin-1/DCC signaling pathway is involved in the migration of most of the IPN populations, mainly affecting those of the Pro and IPR domains of this nucleus. There are psychiatric disorders that involve the medial habenula (mHb)-IPN system, so that this experimental model could provide a basis to study their neurodevelopmental etiology.